2022
DOI: 10.3390/healthcare10122424
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Digital Device Use on Neck and Low Back Pain Intensity among Nursing Students at a Saudi Government University: A Cross-Sectional Study

Abstract: As digital technology and online activities have become more widely accessible over the past few years, information and communication technology have grown in importance in all students’ lives. Most of them routinely use digital devices for a range of activities, primarily for online learning, activities, assignments, conversing, and Internet browsing. This study elucidated the relationship between neck and low back pain intensity and the use of digital devices among Saudi nursing students. A cross-sectional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…These patterns might be partially ascribed to the Saudi Arabian climate, which encourages indoor activities during the hot seasons, and certain sociocultural norms that subtly influence entertainment choices and social interactions, particularly for women. This propensity is further supported by the findings of Mahmoud NA et al [ 22 ], who noted a pervasive daily engagement with digital devices among participants, a trend that starts from an early age, often before thirteen. However, it is crucial to recognize that this behavior is not uniform across the entire population, as variations in lifestyle, access to digital technology, and personal preferences significantly influence individual habits.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These patterns might be partially ascribed to the Saudi Arabian climate, which encourages indoor activities during the hot seasons, and certain sociocultural norms that subtly influence entertainment choices and social interactions, particularly for women. This propensity is further supported by the findings of Mahmoud NA et al [ 22 ], who noted a pervasive daily engagement with digital devices among participants, a trend that starts from an early age, often before thirteen. However, it is crucial to recognize that this behavior is not uniform across the entire population, as variations in lifestyle, access to digital technology, and personal preferences significantly influence individual habits.…”
Section: Discussionsupporting
confidence: 66%
“…All participants owned smartphones, while a quarter also had tablets. In the study “Impact of Digital Device Use on Neck and Low Back Pain Intensity among Nursing Students at a Saudi Government University” by Mahmoud NA et al [ 22 ], it was found that more than half of the respondents were under 22 years old, with an average age of 21.4±1.7 years. Furthermore, more than four-fifths of the respondents in that study were female, and more than one-quarter had progressed to the seventh academic level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant correlation was found between the onset of LBP and a BMI of 25 or greater. A cross-sectional study among Saudi Arabian high school students noted no significant difference in BMI between participants with and without LBP (17) . Oddly, other studies found LBP reported most frequently (58.8%) in students with a normal BMI, with only 14.3% of obese students reporting LBP (25) .…”
Section: Discussionmentioning
confidence: 94%
“…Concerning the occurrence of LBP in relation to gender, a statistically significant correlation is indicated by a p-value of 0.001. A study involving Saudi adolescents revealed that females had a higher LBP prevalence rate at 74%, compared to their male counterparts at 48% (17) . The higher rate among females may be attributed to their smaller body dimensions and lower muscle endurance, potentially making them more susceptible to musculoskeletal pain (MSKP) than males (18)(19)(20)(21) .…”
Section: Discussionmentioning
confidence: 99%